2019
DOI: 10.3389/fncel.2019.00441
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Cerebellar Malformations

Abstract: The cerebellum is well-established as a primary center for controlling sensorimotor functions. However, recent experiments have demonstrated additional roles for the cerebellum in higher-order cognitive functions such as language, emotion, reward, social behavior, and working memory. Based on the diversity of behaviors that it can influence, it is therefore not surprising that cerebellar dysfunction is linked to motor diseases such as ataxia, dystonia, tremor, and Parkinson’s disease as well to non-motor disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 292 publications
(331 reference statements)
1
30
0
Order By: Relevance
“…Therefore, although animals that survived neonatal ZIKV infection with PRVABC059 do not exhibit overt microcephaly, they do have reduced cerebellar volume and increased cerebellar fluid. Importantly, multiple studies have shown that defects in cerebellum can affect not only balance and coordination, but language, emotion, social behavior and working memory as well [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although animals that survived neonatal ZIKV infection with PRVABC059 do not exhibit overt microcephaly, they do have reduced cerebellar volume and increased cerebellar fluid. Importantly, multiple studies have shown that defects in cerebellum can affect not only balance and coordination, but language, emotion, social behavior and working memory as well [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some children who have tumor resection surgery for medulloblastomas, a type of cerebellar tumor, also exhibit symptoms of CCAS [27] and some experience posterior fossa syndrome (PFS). PFS is characterized by a similar but often more severe constellation of symptoms including mutism, emotional lability, ataxia, hypotonia, and behavioral disturbances [28,29]. While the acute, severe presentation of PFS often resolves with time, children who experience PFS often suffer long-term neurocognitive impairment [30][31][32].…”
Section: Cerebellar Injury and Cognitive Impairments In Humansmentioning
confidence: 99%
“…Cerebellar development follows a protracted developmental timeline compared to the cerebral cortex [11, 12, 28]. The first cerebellar neurons are born during mid embryogenesis, but neurogenesis and differentiation of the late-born granule cells, which are the most populous cell type in the brain, occurs during gestational weeks 20–40 in humans and postnatally in rodents (shown in Fig.…”
Section: Development Of the Cerebellar Circuitmentioning
confidence: 99%
“…The Purkinje cell is one of the largest neurons in the brain. It has a large cell body and a unique and distinguishable dendritic tree that produces a γ-aminobutyric acid (GABA) inhibitory neurotransmitter, while granule cells have a small somata and produce glutamate, an excitatory neurotransmitter (for review see Gill and Sillitoe, 2019 ). In rats, neurons of the deep nuclei and Purkinje cells are generated in the ventricular zone on embryonic day (E) 14 and E15, and granule cells proliferate from the caudal part of the ventricular zone known as the rhombic lip (Altman and Bayer, 1985a , b , c ; Hausmann et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%